A (des)proteção social de crianças e adolescentes no contexto de governamentalidade neoliberal de caris neofacista no Brasil - Dorneles, Alexia (2022)
This thesis has the goal to investigate the repercussions in social protective of children and teenagers facing the attack of human rights in the rise of the contexto of neoliberal governability in caris neofacist in Brazil, in perspective to contribute for the resistance process in defence of human right for chidren and teenagers. This a quantitative-qualitative research, of exploratory sequential strategy and descriptive, oriented by the dialect-critical method, grounded on historical materialism. The data treatment was done through the discursive textual analysis based in Roque Moraes (2003) among others. The documental research involved six normative tools: draft bills, proposed amendments to the Constitution and decree laws, which suggest changes that represent threats to childhoods and adolescences in Brazil; thirteen speeches of representatives from the executive power and civil society manifestations about the attack and protection of human rights, available in websites which are instruments of mass opinion formation, posses bias of denouncement/defense and attack to human rights and receive many differents conceptions about the investigated topic; social indicators about education, violation of human rights, socio-educational system and intentional violent deaths, collected from national and international agencies sites that perform semestrial and annual studies about the topic, in the perspective to demonstrate the conditions of access to human rights and highlight possible progress and setbacks in the realization of this rights. The results show that the speeches on course about human rights reiterate the social (de)protection of children and teenagers, which the neoliberal rationality of neofascist nature justifies, because sometimes it hides and sometimes it naturalizes the roots of social inequality in the Brazilian reality. In contrast, the civil society manifestations facing the threats to the stay of human rights, form a counter-hegemony, without which the setbacks would be immeasurable. The normative alteration proposals confirm the temporariness of human rights; intend their suppression; represent the attempt of commodification and highlight the absence of neutrality in the creation processes of drafting legislation, law which are guided by the interests of economic power owners and do not represent solutions for the inequalities and disfunctions caused by the neoliberal order. The study about social indicators showed the tragic exposure of children and teenagers to expressions of the social issue and severe human rights violations, which are aggravated when these particularities are considered: social level, race, age, gender identity, sexual orientation, territorial origin among other social indicators and inequality to human rights access.